Assessing the Determinants of Students' Intentions to Enroll in Higher Education: The Impact of Social Media, University Image, E-WOM, and Tuition Fees - Sujatmiko, Fransiskus Deo Immanuel; Aditya, Addin (Jurnal Teknologi dan Manajemen Informatika, 2024)
University is the level of further education after high school. Several aspects need to be considered by students before deciding to continue to higher education. The purpose of this study is to find, analyze and prove the effect of E-WOM, university image, tuition fees, and social media on student’s intentions. Multiple linear regression analysis was used to analyze the relationship between 4 independent variables and 1 dependent variable. The sampling method used a purposive sampling approach with a total of 100 respondents, and data processing was done computationally. From the results of the study it was revealed that the Electronic Word of Mouth variable had a positive but not significant effect, the university image variable had a positive and significant effect, the social media variable had a significant positive effect, and the education cost variable had a positive but not significant effect on student’s intentions, all variables were independent has a positive effect simultaneously, and from the results of the dominance test, the social media variable (X2) is the most dominant variable.